Innovative Approach to Managing Risks and Facilitating Intra- Regional Trade during COVID-19 Pandemic in the Caribbean Region: A powerful tool to facilitate trade as a stimulus to expand agriculture production and enhance food and nutrition security in the COVID-19 emergency - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
Guide for the systematization of successful initiatives to address the COVID-19 public health pandemic impacts on agriculture and food security.